PENGEMBANGAN GAME DIVISION ADVENTURE BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN MOTIVASI BELAJAR SISWA PADA MATERI OPERASI PEMBAGIAN - Widyyatun Ni'amah, Ika; Ramdhani, Sendi; Andri Nurcahyono, Novi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) describe students' needs for the Division Adventure game to improving their problem-solving skills in division operations, (2) describe the development of the Division Adventure game in improving problem-solving skills in division operations. (3) develop a Division Adventure game that is feasible, practical, and effective in improving problem-solving skills in division operations, and (4) develop a Division Adventure game that is effective in increasing student’s learning motivation. This research is a developmental study consisting of preliminary study, development, and product testing stages. The results of this study are: (1) interactive media is needed that provides a more concrete display, can be used independently by students, improves understanding of story problems, division operations, and learning motivation, which underlies the development of Android-based educational games; (2) the development stage develop an Android-based game consist of four main menus, that are Materi, Latihan, Main, and Pengaturan, and two additional menus, which are Penghargaan and Tentang; (3) A Division Adventure game is feasible based on expert judgements, practical for use in learning based on user responses by students and teachers, and effective in improving problem-solving skills related to division operations that shown by the test results with a t-count = 16.335 > t table = 2.093, which means there is a significant difference in students' problem-solving skills before and after using the Division Adventure game; (4) At the product testing stage, the results obtained were |t count| = 18.007 > t table = 2.093, indicating a significant difference in student learning motivation before and after using the Division Adventure game.